Utilization and Optimization of Beta-Blockers on Heart Failure Patients with Reduced Ejection Fraction (HFrEF) at Cardiac Clinic of Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia: A Cross-Sectional Study - Demissie Z; Mekonnen D (Research Reports in Clinical Cardiology, 2023)
Zekewos Demissie,1 Desalew Mekonnen2 1Department of Internal Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Internal Medicine, Division of Cardiology, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Zekewos Demissie, Email zakdem61@gmail.comIntroduction: Optimal use of guideline-directed medical therapy (GDMT) is an important strategy in preventing cardiovascular morbidity and mortality from heart failure (HF). The use of beta blockers (BBs) is an important pillar of GDMT. The utilization and optimization of BBs are understudied in Ethiopia.Patients and Methods: A hospital-based cross-sectional study was conducted at the cardiology clinic of Tikur Anbessa Specialized Hospital on the utilization and optimization of BBs in the management of HFrEF patients from August 2022 to October 2022 G.C. Patients with a baseline HFrEF diagnosis and who had follow up for at least six months were included in the study. Patients were recruited during their routine clinic visit using systematic random sampling and consent was obtained from all participants. A total of 271 participants were included in this study. The optimal dose of BBs was predefined according to the 2021 European Society of Cardiology HF guideline. Data were collected through patients interview and reviewing the patient’s electronic medical records. The Collected Data was analysed using SPSS version 26.0.Results: The study found BB utilization in 214 (79%) patients. Among the patients taking BBs only 102 (37.6%) participants were on guideline-recommended BBs. The other 41% of patients taking BBs were on Metoprolol tartrate (34.7%) and Atenolol (6.6%), which are not guideline-recommended BBs and these findings signify underutilization of guideline-recommended BBs. Duration of treatment follow-up for more than 1 year, absence of peripheral edema, presence of atrial fibrillation and diuretic use were positively associated with BB utilization.Conclusion: Even though guideline-recommended BB at optimal doses exerts a clinical benefit, this study points out guideline-recommended BBs are underutilized and more importantly used at suboptimal doses among the study participants. To achieve the desired clinical benefit, physicians should attempt to provide guideline-recommended BBs at the optimum or maximum tolerable dose.Keywords: heart failure, beta blocker, Tikur Anbessa Specialized Hospital, optimal therapy